The etiology, pathogenesis, clinical presentation and differential diagnosis in Lower Back Pain with comparison of possible methods of treatment - Kaja Surowiecka; Michał Urbaś; Dawid Kościołek; Aleksandra Kościołek; Jakub Misiak; Martyna Kępczyk; Miłosz Ojdana; Konrad Szalbot; Konrad Czchowski; Alicja Chrościcka (Journal of Education, Health and Sport, 2024)
Introduction and purpose